Revision of the genus Pseudolebinthus (Orthoptera, Gryllidae, Eneopterinae) with the description of a new species from Southeast Africa - Jaiswara, Ranjana; Dong, Jiajia; Robillard, Tony (Zootaxa, 2018)
Pseudolebinthus is an intriguing genus of the tribe Xenogryllini with a distribtuion restricted to southeast Africa and characterized by unique morphological features such as asymmetrical male forewings and harp veins shaped as elongated balloons. It is sister group to the widely distributed genus Xenogryllus and has been known by two species, P. africanus Robillard, 2006 and P. whellani Robillard, 2006. The genus was initially diagnosed based exclusively on male morphological features. In this study, we add a new species to the genus, P. gorochovi Robillard sp. nov. and revise the diagnostic features using both male and female characters. We also update identification keys for the species of the genus.